A holistic approach to diversity recruiting in state police agencies - Williams, Frederick A. (Journal of crime and justice, 2023)
This qualitative study seeks to fill a gap in the literature by providing state police agencies with specific strategies to improve diversity recruitment and hiring. Enhanced agency legitimacy is discussed as a potential by-product of creating a more diverse workforce. The intent of this study is not to evaluate legitimacy or prove diversity recruitment will positively affect the overall perceptions of agency legitimacy. Seven focus groups of sworn female (n = 15) and minority (n = 23) state police officers from a mid-south state police agency are organized to provide insight into diversity recruiting challenges and strategies. We conducted thematic analysis to isolate the themes from the focus groups. The themes resulted in a compilation of diversity recruitment strategies. Additional strategies were added based on the literature. Recommendations are provided for improving diversity recruitment and hiring within state police agencies through a holistic approach.